The impact of digital storytelling on vocational undergraduates’ willingness to communicate in English the mediating role of learning motivation and self-efficacy in a structural equation modelling framework - Luxi, Lu; Samad, Arshad Abdul; Othman, Wan Mazlini (Edelweiss Applied Science and Technology, 2026)
This study aims to examine the structural relationships among self-regulation, self-efficacy, and willingness to communicate in English among Chinese vocational undergraduate EFL learners, with particular attention to the mediating role of self-efficacy in the self-regulation–willingness to communicate pathway. A quantitative replication-and-extension design was adopted. Data were collected from 360 vocational undergraduate students aged 18–22 from six vocational institutions in eastern and southern China through one-stage cluster sampling. After proficiency homogenization, participants completed validated questionnaires, and the data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4.0. The findings revealed significant positive relationships among self-regulation, self-efficacy, and willingness to communicate. Self-regulation significantly predicted both self-efficacy and willingness to communicate, while self-efficacy also significantly predicted willingness to communicate and mediated the relationship between self-regulation and willingness to communicate. The study concludes that self-regulation and self-efficacy are important psychological predictors of communicative readiness among vocational EFL learners. These findings suggest that vocational English instruction should integrate self-regulatory training and efficacy-enhancing strategies to improve communicative competence and better support students’ professional development.